2013
DOI: 10.7763/lnse.2013.v1.80
|View full text |Cite
|
Sign up to set email alerts
|

Circle Marker Based Distance Measurement Using a Single Camera

Abstract: Abstract-A new distance measurement method with the use of a single camera and a circle marker is presented. The distance measurement is based on the idea that a circle marker at a longer distance forms a smaller image when the parameters of the imaging system remain unchanged. Firstly, the image region of the circle marker is segmented and rotation correction algorithm is designed and applied to recover the supposed image region when the circle marker is perpendicular to the camera optical axis. The distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The number of cameras used in some of these studies varies. One study uses a single camera called the triangle similarity for object [18]/marker to distance camera method [19][20][21][22]. Other studies have shown the use of more than one camera, known as a stereo camera [23,24].…”
Section: Research Methods 31 Distance Measurement Systemmentioning
confidence: 99%
“…The number of cameras used in some of these studies varies. One study uses a single camera called the triangle similarity for object [18]/marker to distance camera method [19][20][21][22]. Other studies have shown the use of more than one camera, known as a stereo camera [23,24].…”
Section: Research Methods 31 Distance Measurement Systemmentioning
confidence: 99%
“…The approach in [4] uses the principle of similar triangles to calculate the distance between the object and the camera. As simultaneously estimating depth information, our algorithm can directly obtain the distance from the depth of marked points.…”
Section: Distance Estimationmentioning
confidence: 99%
“…Besides the aforementioned approaches, some other works attempted to address this challenging problem by making use of some auxiliary information. Some markerbased methods [2,26] first segmented markers in the image then estimated distance using the marker area and camera parameters. Instead of utilizing markers, Feng et al [8] proposed a model to predict physical distance based on a rectangular pattern, where four image points of a rectangular were needed to compute the camera calibration.…”
Section: Related Workmentioning
confidence: 99%